Model Manajemen Perubahan untuk Implementasi Sistem Informasi - Nuri Aslami; M. Adhie Husni (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Information systems are used for academic, learning and administrative processes in education. Information systems implementation requires processes and stages and interrelated with another. In implementation process, failure may occur which cause losses in material, time, and other resources. Furthermore, process of implementing information systems also has an impact that needs to be considered, namely changes. The success of an organization in implementing information systems be affected by changes management level, so needs guideline to manage these changes. This paper proposes change management model in implementation of information systems adopted from 3 existing change management models, 7 steps McKinsey, 8 steps Kotter, and Prosci ADKAR. Aspects of proposed change management model are based on critical success factors of change management from previous studies so that new change management model is obtained which consists of 8 domains and 20 aspects. By knowing things to consider in managing change, domains, aspects and factors that affect success of change management, this model can help to achieve objectives in information systems implementation.